2021
DOI: 10.3390/cryst11111293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Content of Phosphorus Slag Composite Concrete: Heat Evolution, Sulphate-Corrosion Resistance and Volume Deformation

Abstract: Phosphorus slag (PS) and limestone (LS) composite (PLC) were prepared with a mass ratio of 1:1. The effects of the content of PLC and the water/binder ratio on the mechanical properties, durability and dry shrinkage of concrete were studied via compressive strength, electric flux, sulfate dry/wet cycle method, saturated drainage method, isothermal calorimeter, adiabatic temperature rise instrument and shrinkage deformation instrument. The results show that PLC can greatly reduce the adiabatic temperature rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…• C in an electric furnace to be melted and then the remained melt by-product is quenched in water to develop the granular phosphorous slag [8][9][10]. One of the most beneficial alternatives to Portland cement (PC) is blended cements, i.e., hydraulic cements consisting of a homogeneous blend of cement and other supplementary cementitious materials (SCM).…”
Section: Introductionmentioning
confidence: 99%
“…• C in an electric furnace to be melted and then the remained melt by-product is quenched in water to develop the granular phosphorous slag [8][9][10]. One of the most beneficial alternatives to Portland cement (PC) is blended cements, i.e., hydraulic cements consisting of a homogeneous blend of cement and other supplementary cementitious materials (SCM).…”
Section: Introductionmentioning
confidence: 99%
“…A high concentration produced more hydrotalcite than C-A-S-H as intensive reaction at the early stage hindered the growth of C-A-S-H in the later stage, and decreased the Al/Si ratio and polymerization of C-A-S-H, which led to a low strength. Phosphorus slag and limestone composite (PLC) can greatly reduce the adiabatic temperature rise, chloride permeability and drying shrinkage of concrete, but do not affect the long-term strength of concrete [4]. Guan et al [5] identified the possible problems of coal gangue as a road base via an unconfined compressive strength test, a splitting test, a freeze-thaw test and a drying shrinkage test of cement-stabilized gangue with varying cement amounts.…”
mentioning
confidence: 99%